The Project of Social Skills Development in the Career Education for Students with Mental Health Problems - Urtāne, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Latvian education system has seen many changes that have been influenced on the structure, content and teaching methods which provide skills to use the knowledge acquired to cope with changes. Latvia has become a knowledge-based society, so the school offered the working methods that ensure students 'social skills and their level of resistance and promotes students' career education. The abstract summarizes the the most effective theoretical methods of working with students with mental health problems - the project work methods and the reachment of social skills in the career education. The research was done at Adamova Special Boarding School for students with mental health problems. At the projects students have learned to organize themselves independently, to take responsibility, to organize their time, to be able to follow the rules, learned to express their thoughts orally and in writing forms, the ability to evaluate themselves and to cooperate with others. At school the questionnaire was been done, where the teachers and students were asked in order to define the situation of social skill competence in the career education.